And finally : matters of life and death - Marsh, Henry, 1950- (St. Martin's Press, 2023)
"From the bestselling neurosurgeon and author of Do No Harm, comes Henry Marsh's And Finally, an unflinching and deeply personal exploration of death, life and neuroscience. As a retired brain surgeon, Henry Marsh thought he understood illness, but he was unprepared for the impact of his diagnosis of advanced cancer. And Finally explores what happens when someone who has spent a lifetime on the frontline of life and death finds himself contemplating what might be his own death sentence. As he navigates the bewildering transition from doctor to patient, he is haunted by past failures and projects yet to be completed, and frustrated by the inconveniences of illness and old age. But he is also more entranced than ever by the mysteries of science and the brain, the beauty of the natural world and his love for his family. Elegiac, candid, luminous and poignant, And Finally is ultimately not so much a book about death, but a book about life and what matters in the end."--